Evidence of Overfishing in Small-Scale Fisheries in Madagascar - Gough, Charlotte L. A.; Dewar, Katrina M.; Godley, Brendan J.; Zafindranosy, Erude; Broderick, Annette C. (Frontiers in Marine Science, 2020)
Small-scale fisheries are an important source of food, income and cultural identity to millions of people worldwide. Despite fishers observing declining catches, a lack of data remains a barrier to understanding the status of small-scale fisheries and their effective management in many places. Where data exist, complex analyses and stock assessments are often beyond the capacity and budgets of local managers. Working with small-scale fisheries in western Madagascar, we analyse landings data to provide a description of the fishery and evaluate the top twenty commonly caught species for evidence of overfishing. Using length composition data, we use Froese’s three simple rules: Let them spawn, let them grow and let the mega-spawners live and Cope and Punt’s decision tree to infer overfishing. We also use length-based parameters to calculate and compare fishing mortality with natural mortality to assess overfishing (F>M). Over 17,000 fishing trips were registered, landing just short of 2 million individual fish. Length data were recorded for a sample of over 120,000 individuals. Fish comprised 95% of landings, with the remainder comprised of other groups including crustaceans (mostly shrimp, crab and lobster), cephalopods, and holothurians. We provide some of the first evidence that fish species caught in the small-scale fisheries of the Menabe region of Madagascar are experiencing overfishing. The most notable result that for 13 of the 20 most common species, fishing mortality exceeds natural mortality. Many species had a large proportion of individuals (in some cases 100%) being caught before they reached maturity. Very few species were fished at their optimal size, and there were low numbers of large individuals (mega-spawners) in catches. Overfishing in western Madagascar presents a serious threat to the income, food security and well-being of some of the most vulnerable people in the world. The results of this paper support the call for improved management. However, management approaches should take account of overlapping fisheries and be inclusive to ensure the impacts of management do not undermine the rights of small-scale fishers. Further data are needed to better understand the trends and to improve management but should not hinder pragmatic action.